Reconnaissance Survey of The Wildlife Sanctuary of Stubb’s Creek Forest Reserve, Akwa Ibom State, Nigeria (2004)
This study was conducted at the instance of the Honourable Commissioner, Ministry of Environment, Akwa Ibom State in realization of the need to assess the potentials of wildlife in the Stubbs-creek forest reserve of Akwa-Ibom State, Nigeria. The terms of reference included, but not limited to provision of information on status of fauna and flora in the forest reserve, bearing in mind the level of human interference that had occurred in the last one decade. Using a combination of standard methods wildlife, vegetation and questionnaire surveys were conducted in and around the forest reserve to obtain information on the status of the major plant and animal lives and the various sources of threat to their sustainable management. Results obtained from the study indicate large- scale disturbance of the biophysical environment (flora and fauna) arising from such human activities as farming, illegal logging, oil prospecting and exploration. These have affected the hitherto rich fauna and flora of the reserve. The study still identified the existence of over 80 important plant species, which include Alcornea cor difolia; Raphia spp; Anthocleista nobilis;; Rhizophora racemosa; Gmelina arborea; Costus afer; Chromolina odorata; Rauvolvia vomitoria; Calamus spp; Musanga cercopioides; Albizia spp; Selaginalea spp. Species with moderate frequency of occurrence include Carpolobia lutea; Napoleona vogelii; Allablackia floribunda. They were distributed within the natural lowland rainforest, oil palm and raphia bushes and the mangrove. Over 90 animal species including rodents, reptiles, birds and monkeys were encountered. They include Thryonomys swinderianus, Potamochoerus porcus, Trangelaphus scripus; Python sebae, Crocodilus spp, Neophron monachus, Milvus migrans, Streptopelia senegalensis, Apus affinis,, Egretta alba, Ardeola ibis, Scopus umbretta, Neophron monachus The potential of the wildlife sanctuary for ecotourism is still quite high particularly with the existence of oil prospecting and exploration concerns that attract heavy human traffic into the area. Also there exist standard hotels within 30km radius of the forest reserve, which will encourage visitors to combine business with pleasure. There is however the urgent need to: secure the boundaries of the sanctuary, carry out a feasibility study and environmental impact assessment with a view to having comprehensive information that will form the basis for re-investment by the State government and also set the template for the development of proposals for donor assistance from international donor/investment agencies, win the confidence of the settlers in the adjoining communities, seek local and external partnerships for the management of the sanctuary and; Finally, the institutional and legal frameworks of the reserve should be clearly spelt out to enhance sustainability. The Sanctuary has the potential to boost the Poverty Reduction Strategy Programme (PRSP) of the State Government and should therefore be rehabilitated